Workplace Stressors and SME Sustainability in Malaysia: A Conceptual Framework Linking Human Capital and Employee Performance - Ahmad Suryanto, Leny Cahyati (Journal of Technology Management and Technopreneurship (JTMT), 2025)
This conceptual paper constructs a paradigm that associates workplace stressors with SME sustainability in Malaysia, mediated by human capital and modulated by social support, with employee performance as the immediate outcome. The research, grounded in the Job Demand-Control-Support (JDCS) model and Social Exchange Theory (SET), posits that stressors such as elevated job demands, ambiguous roles, inadequate compensation, and restricted autonomy adversely affect employee performance in Malaysian SMEs with little resources, exacerbated by informal structures. Human capital, encompassing skills, knowledge, health, and motivation, contributes to the transformation of performance into triple-bottom-line sustainability (economic, social, and environmental). Social support from supervisors, coworkers, and family also helps by giving people greater resources and motivating them to help one other. Using integrative review methods, the framework comes up with testable ideas that fit with Malaysia’s policy focus on making small and medium-sized businesses more resilient and making transitions that are good for the environment. The implications underscore the necessity for SMEs to incorporate stress management, supporting practices, and capacity-building HR systems to protect productivity and fulfill sustainability requirements within the supply chain. It is advisable to do future empirical testing through structural equation modeling to corroborate these routes within Malaysian contexts.